1999
DOI: 10.1074/jbc.274.15.10489
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Gap Junctional Communication by the Platelet-derived Growth Factor Is Mediated via Multiple Signaling Pathways

Abstract: The platelet-derived growth factor (PDGF) mediates its cellular functions via activation of its receptor tyrosine kinase followed by the recruitment and activation of several signaling molecules. These signaling molecules then initiate specific signaling cascades, finally resulting in distinct physiological effects. To delineate the PDGF signaling pathway responsible for the disruption of gap junctional communication (GJC), wild-type PDGF receptor ␤ (PDGFR␤) and a series of PDGFR␤ mutants were expressed in T51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 78 publications
(97 reference statements)
2
36
1
Order By: Relevance
“…These reductions were reflected in significant losses of Cx43 protein at cellular borders. Such findings are especially interesting in the light of suggestions by previous workers that activation of the ERK signalling pathway leads to hyperphosphorylation of Cx43 and that this in turn leads to reductions in GJIC (Hossain et al, 1998a;Hossain et al, 1999b;Kanemitsu and Lau, 1993;Warn-Cramer et al, 1998;Warn-Cramer et al, 1996).…”
Section: Discussionmentioning
confidence: 81%
“…These reductions were reflected in significant losses of Cx43 protein at cellular borders. Such findings are especially interesting in the light of suggestions by previous workers that activation of the ERK signalling pathway leads to hyperphosphorylation of Cx43 and that this in turn leads to reductions in GJIC (Hossain et al, 1998a;Hossain et al, 1999b;Kanemitsu and Lau, 1993;Warn-Cramer et al, 1998;Warn-Cramer et al, 1996).…”
Section: Discussionmentioning
confidence: 81%
“…The synergistic action of PDGF-BB and cAMP-elevating agents on Cx43 expression and GJIC was unexpected, because PDGF-BB has been described as a potent inhibitor of GJIC (14,15,40). Counteracting effects between PDGF-BB and cAMP-elevating agents in the control of cell growth, migration, and other cell behaviors have been extensively documented (18,21,26), whereas little is known about the synergism between PDGF-BB and cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…PKC is another important molecule implicated in the disruption of GJIC by PDGF-BB (14,15). To explore the role of PKC in our system, we assessed Cx43 expression in the presence of the PKC inhibitor calphostin C or under conditions of depletion of PKC by pretreatment with 12-O-tetradecanoylphorbol 13-acetate (10 Ϫ6 M) for 24 h (14).…”
Section: Potentiating Effect Of Pdgf-bb On Cx43 Expression Is Mediatementioning
confidence: 99%
See 1 more Smart Citation
“…A number of potential consensus sites for both serine/threonine and tyrosine kinases can be identified. Detailed biochemical studies have shown that Cx43 acts as a substrate for phosphorylation by v-Src (7,8), protein kinase C (PKC) and mitogen-activated protein kinase (MAPK) (9)(10)(11). Recent evidence also suggests that Cx43 was phosphorylated by the mitosis-associated cdc-2 kinase (12) and cGMP-dependent phosphorylation of rat Cx43 has also been demonstrated (13).…”
Section: Introductionmentioning
confidence: 99%